Os direitos sexuais nas ruínas do neoliberalismo e neoconservadorismo : um panorama crítico acerca da cidadania LGBTI na democracia brasileira (1986-2020) - Oliveira, Brendhon Andrade (2021)
This dissertation communicates results of research carried out under the Graduate Program in Law at the Federal University of Mato Grosso, between the years 2019-2021, with funding from the Coordination for the Improvement of Higher Education Personnel (CAPES/MEC). The chosen theme is the rights of the LGBTI population, delimiting the construction of citizenship in this community in the context of the three democratic powers post-Constituent of 1986/87. In this sense, it starts with the following question: how was the trajectory of rights and specific public policies for the LGBTI community constituted in the Brazilian context? Therefore, the main objective of the research is to analyze the trajectory of LGBTI human rights rights and public policies in Brazil (1986-2020). The research is qualitative and manipulates the hypothetical-deductive method, based on pre-established hypotheses, which in this paper consider: a) LGBTI human rights policies are marked by weaknesses and resistance of public morality, impacting their effectiveness; b) there is an anti-gender crusade institutionalized in the Legislative Power that prevents the approval of sexual and reproductive rights and equal participation in decision-making; c) with this scenario, LGBTI demands will be shifted to the Judiciary, which will recognize the rights. For this task, document analysis is used as a data collection technique, including among the main documents Programs and Annals in relation to public policies, bills and other denominations of the legislative process, and judicial decisions and judgments about judicialization of LGBTI rights. For data analysis, content analysis is used as a technique that reveals the intentions in the written messages. Bibliographic research is used, making use of theoretical contributions from studies in the legal, feminist, queer, gay and lesbian, decolonial, Foucaultian and Marxist fields, in view of the thematic complexity. Furthermore, it walks in conclusive directions that the citizenship achieved is precarious, not meeting the basic needs of the LGBTI community, considering that LGBTIphobia is structural, preventing the realization and effectiveness of rights in democratic institutions.